Export performance, governance, and economic growth: Evidence from Fiji - a small and vulnerable economy - Ronal Chand; Rup Singh; Arvind Patel; Devendra Kumar Jain (Cogent Economics & Finance, 2020)
This article analyses the nexus between exports, established indicators of governance, and economic growth in Fiji. It finds that exports and governance co-operate to promote economic growth. The interplay between these variables is also meaningful. The findings imply that Fiji needs to improve export productivity and quality of institutional governance to ensure persistent rates of economic growth. Other variables such as human capital, private investment, foreign aid, and policy environment are also growth-enhancing in this small and vulnerable economy.
Keywords: A12; B13; B22; B40; 330; economic growth; Fiji; governance index; governanceexport performance; small and vulnerable economies